PERUBAHAN SOSIAL BUDAYA EKONOMI MASYARAKAT TRANSMIGRSI DARI JAWA DENGAN MASYARAKAT SETEMPAT DI DESA BUNGARAYA KECAMATAN BUNGARAYA KABUPATEN SIAK (1980-2010) - Khairul Asri; Isjoni Isjoni; Bedriati Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: Transmigration can be seen as one of the elements of an experimental framework which is very important in land use efforts in Indonesia. This is attributed to the explosion of the population in Java and Bali. Therefore one of the allegations in Indonesia that the target of trasmigration is the population of Java. One of the areas that became the center of transmigration was the Village of Bungaraya. The purpose of this study is 1) To find out the forms of livelihoods of local communities and Javanese transmigrant communities in Bungaraya. 2) To find out the economic development of the local transmigrants and Javanese transmigrants in the village of Bungaraya. 3) To see the socio-economic differences of the local people and transmigrants from Java. As for this study using qualitative and quantitative methods and data obtained from the results of interviews coupled with questionnaire / consensus questionnaire and data from the Bungaraya Village office. The results of this study are that there are enormous benefits to the socio-economic and even cultural aspects of the community both from the transmigration community from Java and the local community. In addition, the mindset of the community both from the transmigration community from Java and the local community has progressed as can be seen from changes in health education. the more advanced.Key Words:Change , Social, Culture, Economy, Transmigration